Extended range of the Lockheed Martin coax Micro cryocooler. (March 2016) - Frank, D.; Champagne, P.; Will, E.; Kaldas, G.; Sanders, L.; Roth, E.; Olson, J.R.
Highlights: The performance range of the Lockheed Martin Micro cryocooler was extended. The cryocooler thermal mechanical unit is at Technology Readiness Level (TRL) six. Environmental testing included thermal vacuum and random vibration. Abstract: This paper describes the higher cooling capability of the Lockheed Martin coax Micro cryocooler thermal mechanical unit. The design of the previously qualified TRL6 Micro (Nast et al., 2014)[1] was modified to accommodate over twice the input power, greatly increasing the cooling capability. These Micro units are in a split configuration with the cold head separated from the compressor. This unit was optimized for cooling at 105 K and provides cooling over a wide range of temperatures. With a weight below 450 g, this small unit is ideal for compact instruments. Load lines were obtained over a range of powers, cold tip temperatures and rejection temperatures. This testing raised the Technology Readiness Level to six.